2020
DOI: 10.1080/07391102.2020.1835729
|View full text |Cite
|
Sign up to set email alerts
|

Screening of phytochemicals as potent inhibitor of 3-chymotrypsin and papain-like proteases of SARS-CoV2: an in silico approach to combat COVID-19

Abstract: COVID-19 and its causative organism SARS-CoV2 that emerged from Wuhan city, China have paralyzed the world. With no clinically approved drugs, the global health system is struggling to find an effective treatment measure. At this crucial juncture, screening of plant-derived compounds may be an effective strategy to combat COVID-19. The present study investigated the binding affinity of phytocompounds with 3-Chymotrypsin-like (3CLpro) and Papain-like proteases (PLpro) of SARS-CoV2 using in-silico … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 60 publications
4
46
0
Order By: Relevance
“…The time step was set to 1.25 fs, and after every 100 ps, the simulation trajectories were saved. The simulation trajectories were analyzed to calculate the root-mean-square deviation (RMSD), root-mean-square fluctuation (RMSF), the radius of gyration (Rg), solvent-accessible surface area (SASA), and hydrogen bonds [ 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…The time step was set to 1.25 fs, and after every 100 ps, the simulation trajectories were saved. The simulation trajectories were analyzed to calculate the root-mean-square deviation (RMSD), root-mean-square fluctuation (RMSF), the radius of gyration (Rg), solvent-accessible surface area (SASA), and hydrogen bonds [ 67 ].…”
Section: Methodsmentioning
confidence: 99%
“…To the best of our knowledge, there are no other MD simulations of paritaprevir–RBD and amentoflavone–RBD complexes. But, there are many stable MD simulations of the amentoflavone complex with the main protease (Ghosh et al, 2020 ; Lokhande et al, 2020 ; Mishra et al, 2020 ; Patil et al, 2021 ; Saravanan et al, 2020 ; Swargiary et al, 2020 ). For paritaprevir and simeprevir, stable MD simulations with the main protease and the uridylate-specific endoribonuclease (NSP15) have been obtained (Alamri et al, 2020 ; Khan, Jha, Amera, et al, 2020 ; Khan, Jha, Singh, et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…There are also studies searching for inhibitors for RNA-dependent RNA polymerase (Elfiky, 2020 ), papain-like protease (Ibrahim et al, 2020 ), and RNA endoribonuclease (Khan, Jha, Singh, et al, 2020 ; Sharma et al, 2021 ). In many works, a multitarget approach was used (Albohy et al, 2020 ; Chikhale et al, 2020 ; Khan, Jha, Amera, et al, 2020 ; Maffucci & Contini, 2020 ; Mishra et al, 2021 ; Patil et al, 2021 ; Puttaswamy et al, 2020 ; Rameshkumar et al, 2021 ; Swargiary et al, 2020 ). Despite the large number of drug-repurposing studies against SARS-CoV-2, there is little agreement about the identified hit candidates and almost no experimental validation of the results (Dotolo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The normal simulation time step of 1.25 fs was maintained. The simulation trajectories were saved after every 100-ps interval, and the simulation was run for 50-ns to analyze RMSD and root mean square fluctuation (RMSF) [ 58 , 59 ]. Imipramine HCl, diazepam, diclofenac-Na, and ascorbic acid were denoted as control 1, control 2, control 3, and control 4, respectively.…”
Section: Methodsmentioning
confidence: 99%